907-P: Clinical Efficacy and Safety of SGLT2 Inhibitors and DPP-4 Inhibitors Combination in Asian Patients with Type 2 Diabetes Inadequately Treated with Metformin—A Systemic Review and Meta-analysis of Randomised Controlled Studies - KHALSE, MANEESHA; SOWMIYA, M K. (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: To analyze the efficacy, safety and tolerability of SGLT2i and DPP-4i combination vs placebo as add-on or initial therapy in Asian patients with T2DM as available data is heterogenous in Asian population. Methods: Database like MEDLINE, Embase, and Cochrane review was searched until August 2023 to identify trials evaluating the efficacy and safety of combination therapy (SGLT-2i+ DPP-4i and/or metformin) in subjects with Asian origin. Primary outcome was mean difference in glycemic and extra-glycemic effects like body weight and systolic BP, and hypoglycemia risk at least for 24 weeks. A meta-analysis was conducted to measure standardized mean differences (SMD), and other relevant statistics for clinical parameters. Meta-analysis with systemic review was performed using CMA v4 software. Results: A total of nine RCTs were included with 2170 patients (three studies as initial combination, three of SGLT2i as add-on to DPP-4i and three of DPP-4i as add onto SGLT2i in a sequential manner). Overall, the combination of SGLT2i and DPP-4i demonstrated a significant decrease in HbA1c relative to DPP-4i [-0.95% (95% CI: -1.09, -0.81)] or SGLT2i [-0.97% (95% CI: -1.11, -0.83)] compared to placebo. When SGLT2i combined with DPP-4i, either as initial or sequential combination, a marked lowering of HbA1c level was reported. Patients treated in combination treatment revealed the favorable effects on the body weight and systolic BP compared to subjects on DPP-4 inhibitors, but no difference in subjects of SGLT2i arm. There were no statistically significant differences in the incidence of adverse events. Conclusion: SGLT2i and DPP-4i combination show significant glycemic improvement in Asian population. Safety indicators did not show significant differences. More high-quality studies are required to validate these findings.